PENGARUH PENERAPAN E-MARKETING DAN KEBIJAKAN CUSTOMER RELATIONSHIP TERHADAP TANGIBLE BENEFIT PADA BANK X (PERSERO)TBK DI JAKARTA - Khadijah, Siti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2011)
This research purposes to determine how far the influences of E-Marketing practice and policy of Costumer Relationship toward Tangible Benefit at Bank X. The theories which are used in this research are theories relating to e-marketing, customer relationship and tangible benefits. E-Marketing theories explain about definition and models of e-marketing. Theories of Customer Relationship show the relation between customer relationship and the costumer itself, relation between e-marketing and customer relationship in understanding the customers, and the benefits reached by e-marketing and customer relationship practice. This research uses associative causal methodology. Independent variable X1 is E-Marketing practice, variable X2 is Customer Relationship policy, and dependent variable (Y) is Tangible Benefit. The object of this research is taken from information based on annual report. The results of this research are; double correlation as amount 0,810 between variable X1, variable X2, and variable Y. Coefficient of determination between variable X1, X2, and Y, which r is 0.810 showing positive and strong connection between variable X1 and variable X2 with variable Y. The highest amount of variable X1 and X2 the highest is variable Y. Double correlation significant test between variable X1, and X2 with Y , where Faccount=1,907>Ftabel (2/5) = 5,79 with significant value as amount 0,344 meant Ha is accepted and Ho is rejected. It means variable X1 and X2 has personally or simultaneously significant influence toward Y.